The 7 pillars of TRIZ philosophies. (August 2020) - Sheu, D. Daniel; Chiu, Ming-Chuan; Cayard, Dimitri
Highlights: Summarize 4 philosophies of traditional TRIZ. Present an enhanced version of TRIZ with 7 fundamental philosophies and effective practical usage. Point out some important directional research opportunities of TRIZ methodology. Abstract: TRIZ, the theory of inventive problem solving, has known as one of the most effective tools for conceiving engineering designs and solving difficult problems. The importance of TRIZ has been acknowledged in various fields where its applications inspire great results. Most researchers focus on the practical usage of the tools or development of the tools without knowing the fundamental philosophies that support TRIZ. Classical TRIZ has only 4 philosophies as pillars of TRIZ. The aim of this paper is to present an augmented version of TRIZ philosophies, and bridge the gap between the guiding fundamental philosophies and effective practical usage. Further, some important directional research opportunities of TRIZ methodology are suggested for future development.